1997
DOI: 10.1074/jbc.272.42.26522
|View full text |Cite
|
Sign up to set email alerts
|

Type VI Collagen Anchors Endothelial Basement Membranes by Interacting with Type IV Collagen

Abstract: Type VI collagen filaments are found associated with interstitial collagen fibers, around cells, and in contact with endothelial basement membranes. To identify type VI collagen binding proteins, the amino-terminal domains of the ␣1(VI) and ␣2(VI) chains and a part of the carboxyl-terminal domain of the ␣3(VI) chain were used as bait in a yeast two-hybrid system to screen a human placenta library. Eight persistently positive clones were identified, two coding the known matrix proteins fibronectin and basement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(227 citation statements)
references
References 45 publications
(57 reference statements)
7
215
1
3
Order By: Relevance
“…The collagen, composed of three different subunits, was found to selfassemble through a staggered disulfide-stabilized tetramer intermediate to microfibrils (Furthmayr et al 1983;Zhang et al 2002). Type VI collagen binds under in vitro conditions to type IV collagen and type I collagen, linking the basement membrane to the adjacent stroma (Bonaldo et al 1990;Kuo et al 1997). It also binds to perlecan.…”
Section: Basement Membranesmentioning
confidence: 99%
“…The collagen, composed of three different subunits, was found to selfassemble through a staggered disulfide-stabilized tetramer intermediate to microfibrils (Furthmayr et al 1983;Zhang et al 2002). Type VI collagen binds under in vitro conditions to type IV collagen and type I collagen, linking the basement membrane to the adjacent stroma (Bonaldo et al 1990;Kuo et al 1997). It also binds to perlecan.…”
Section: Basement Membranesmentioning
confidence: 99%
“…In addition to laminin, type IV collagen is the most abundant glycoprotein in the basement membrane and all together the components of the basement membrane form a thin pericellular matrix that is involved in many cellular functions (gene expression, adhesion, migration, differentiation, and apoptosis) 64,65 . Through its carboxyl-terminal globular domain collagen IV interacts with the amino-terminal domain of the collagen VI alpha-1 chain 65 and this connection is essential for anchoring the basement membrane of the muscular fiber to the other components of the extracellular matrix and maintaining the structural muscle integrity [65][66][67][68] . Collagen VI provides a microfilamentous network in the extracellular matrix of the muscular tissue, as well as in other organs [66][67][68] .…”
Section: Fig 1 Schematic Representation Of the Main Proteins Involvementioning
confidence: 99%
“…Y2H has been used by several laboratories to document interactions between other extracellular matrix proteins, including type IV collagen (24), thrombospondin 1, the laminin ␤3 chain, and the NC1 domain of type VII collagen (25), as well as the microfibrillar protein emilin (26) and MAGP-2 (16). In our assays, Y2H provided a useful way to screen potential binding sites but was not sufficiently precise to unambiguously identify the correct binding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…6B shows that only FBN2Ex (23)(24)(25) retained the ability to bind full-length MAGP-1. To assess whether the EGF domains that flank exon 24 in FBN2Ex (23)(24)(25) are required for its binding to MAGP-1, as was found in the yeast two-hybrid assay, we utilized an expression construct that encoded just Ex24. Ligand blot of bacterially expressed protein demonstrated that exon 24 retains the ability to bind MAGP-1 (Fig.…”
Section: Mapping Of the Magp-1-binding Domain To Fbn2 Exon 24 -Y2hmentioning
confidence: 99%
See 1 more Smart Citation